Exposure of Hyperandrogen During Pregnancy Causes Depression- and Anxiety-Like Behaviors, and Reduced Hippocampal Neurogenesis in Rat Offspring - Cheng, Juan; Wu, Haojuan; Liu, Huawei; Li, Hua; Zhu, Hua; Zhou, Yongmei; Li, Hongxia; Xu, Wenming; Xie, Jiang (Frontiers in Neuroscience, 2019)
The hippocampus is a region in which neurogenesis persists and retains substantial plasticity throughout the lifespan. Accumulating evidences indicate an important role of androgens and androgenic signaling in the regulation of offspring hippocampal neurogenesis and the survival of mature or immature neurons and gliocyte. Hyperandrogenic disorders have been associated with depression and anxiety. Previous studies have found that pregnant hyperandrogenism may increase the susceptibility of the offspring to depression or anxiety and lead to abnormal hippocampal neurogenesis in rats. In this study, pregnant rats were given subcutaneous injection of aromatase inhibitor letrozole in order to establish a maternal hyperandrogenic environment for the fetal rats. The lithium chloride (LICl) was used as intervention agent since previous study has been shown that lithium chloride could promote neurogenesis in hippocampus. The results revealed that pregnant administration of letrozole resulted in depressive- and anxious-like behaviors in the adolescent period. A remarkable decrease in immature nerve cells marked by doublecortin (DCX) and mature neurons co-expressed by Brdu and NeuN in adult years were detected in the hippocampal dentate gyrus of adolescent rats and lithium chloride alleviated the effects on neurobehavioral and promoted the differentiation and proliferation of neural progenitor cells, while, hyperandrogenic intrauterine environment had no effects on astrocyte marked by GFAP in dentate gyrus. Furthermore, Wnt/β-catenin signaling pathway related to normal development of hippocampus was examined, but, there was no significant changes of Wnt signaling pathway members. Our study provides evidence showing that exposure of androgen during pregnancy led to alterations in depressive, anxious and stereotypical behaviors and these phenotypes were possibly associated with changes in neurogenesis in the dentate gyrus.